2020
DOI: 10.1002/berj.3633
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical devices as children’s social care levers: A study of social care workers’ attitudes towards boarding schools to care for and educate children in need

Abstract: It has been proposed that boarding schools in England can be used to provide a stable education and care environment for vulnerable children in need, and the government is expanding their use. However, for vulnerable children to be placed in boarding schools, social workers will need to be willing to contemplate boarding as a viable care option. In this study we interviewed N = 21 social care practitioners including directors, senior and middle managers, frontline social workers, social worker-academics and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…While boarding schools may now have counsellors and modern amenities, it is the separation and rejection, fear, anxiety and the increased likelihood of experiencing abuse and other traumas that are shown to have a detrimental effect on the mental health of boarding students well into adulthood (Duffell & Bassett, 2016, Faulkner, 2020. In the absence of evidence to the contrary we are left with the fact that children being separated from their families is not supported by any child development theory (Duffell & Bassett, 2016) and is considered the last resort by the social care system in Britain (Murphy et al, 2020). NOTES 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While boarding schools may now have counsellors and modern amenities, it is the separation and rejection, fear, anxiety and the increased likelihood of experiencing abuse and other traumas that are shown to have a detrimental effect on the mental health of boarding students well into adulthood (Duffell & Bassett, 2016, Faulkner, 2020. In the absence of evidence to the contrary we are left with the fact that children being separated from their families is not supported by any child development theory (Duffell & Bassett, 2016) and is considered the last resort by the social care system in Britain (Murphy et al, 2020). NOTES 1.…”
Section: Discussionmentioning
confidence: 99%
“…The substitute family could foster an intense loyalty to the school, to the team and to the house in which they lived (Morrell, 1994; Hodges, Sheffield & Ralph, 2013). For some, this provided an enduring sense of security, community, camaraderie and identity (Lambert, 1968); for others, a welcome respite from home (Murphy et al ., 2020). While not wishing to lose sight of these facts, we must also acknowledge those who were mistreated (Schaverien, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The few studies that have been conducted have suggested that the schools can 'be described as "total institutions" that provide through both formal and "hidden" curricula, a strong secondary socialisation model for students that will decisively influence their public and private adult life' (Faguer, 1991, as cited in van Zanten, 2009Gaztambide-Fernández, 2009a;Khan, 2011). In addition, a counternarrative is emerging 'concerned with the significant harm and damage done to the emotional and psychological development of some children that attend boarding schools' (Murphy et al, 2020(Murphy et al, , p. 1317cf. Schaverien, 2015).…”
Section: Boarding Schools Their Alumni and The Case Of Germanymentioning
confidence: 99%